Future of Male Infertility Evaluation and Treatment: Brief Review of Emerging Technology - Diaz, Parris; Dullea, Alexandra; Chu, Kevin Y.; Zizzo, John; Loloi, Justin; Reddy, Rohit; Campbell, Katherine; Li, Philip S.; Ramasamy, Ranjith (Urology (Ridgewood, N.J.), 2022)
Over the past few decades, there have been significant advances in male infertility, particularly in the development of novel diagnostic tools. Unfortunately, there remains a substantial number of patients that remain infertile despite these improvements. In this review, we take heed of the emerging technologies that will shape the future of male infertility diagnosis, evaluation, and treatment. Improvement in computer-assisted semen analyses and portability allow males to obtain basic semen parameters from the comfort of their home. Additionally, breakthrough ultrasound technology allows for preoperative prediction of potential areas of spermatogenesis within the testes, high-resolution optics permits better visualization during microdissection testicular sperm extraction (mTESE), and artificial intelligence improves sperm selection and identification.